The robust finite-volume schemes for modeling nonclassical surface reactions - Čiegis, Raimondas; Katauskis, Pranas; Skakauskas, Vladas (Nonlinear Analysis: Modelling and Control, 2018)
A coupled system of nonlinear parabolic PDEs arising in modeling of surface reactions with piecewise continuous kinetic data is studied. The nonclassic conjugation conditions are used at the surface of the discontinuity of the kinetic data. The finite-volume technique and the backward Euler method are used to approximate the given mathematical model. The monotonicity, conservativity, positivity of the approximations are investigated by applying these finite-volume schemes for simplified subproblems, which inherit main new nonstandard features of the full mathematical model. Some results of numerical experiments are discussed.
Keywords: system of nonlinear PDEs; finite-volume method; conservative approximation; heterogeneous reactions; surface diffusion; spillover